Integrating movement data and behavioural observations to assess the spatial functional role of sympatric cleaner fishes - Pauline Narvaez; Alexandra S. Grutter; Renato A. Morais (Animal Behaviour, 2025)

First report of interspecific cleaning in a Pseudochromid, the dusky dottyback (Pseudochromis fuscus) - William E. Feeney; Rohan M. Brooker; Alexandra S. Grutter; Matthew D. Nicholson (Marine Biodiversity, 2023)

Corrigendum: Cleaner fish Labroides dimidiatus presence does not indirectly affect demersal zooplankton - Alexandra S. Grutter; Natsumi Nishikawa; Julian Uribe-Palomino; Anthony J. Richardson (Frontiers in Marine Science, 2023)

Cleaner Fish Labroides dimidiatus Presence Does Not Indirectly Affect Demersal Zooplankton - Alexandra S. Grutter; Natsumi Nishikawa; Julian Uribe-Palomino; Anthony J. Richardson (Frontiers in Marine Science, 2022)
Coral reef mutualisms involve complex trophic ecological relationships that produce indirect effects. Excluding mutualistic cleaner fish Labroides dimidiatus from reefs indirectly increases the abundance of many fishes and reduces demersal stages of their ectoparasitic prey (gnathiid isopods). Whether cleaners affect populations of planktivorous fishes that consume demersal zooplankton, and consequently indirectly affect the rest of the demersal zooplankton community — via presumed changes in planktivory — is unknown. Therefore, using a long-term cleaner fish manipulation on patch reefs (July 2000 to December 2012, Great Barrier Reef), we tested whether cleaner treatment (removal or control) affects planktivorous fish abundance and diversity, and demersal zooplankton biomass, abundance, and diversity. Fish surveys, 9 and 12 years after removing cleaners revealed fewer fish on removal compared to control reefs for one of the three most abundant planktivores, but not total abundance (Pomacentridae, 26 species), diversity, and composition. Emerging zooplankton were sampled during the day and night over nine sampling trips across 12 years. There was no effect of cleaner treatment on post-removal values, compared with pre-removal values in July 2000, for zooplankton biomass, abundance, diversity, and composition (34 taxa). Zooplankton abundance showed no diel differences, but diversity, and occasionally biomass, were higher at night. Zooplankton composition also showed diel differences, with three taxa contributing the most to this dissimilarity [Cirripeda nauplii, Facetotecta (Arthopoda), Oikopleuridae (Chordata)]. Zooplankton diversity did not differ among times, abundance was higher in January 2002 relative to July 2000, and composition differed among all times. The lack of detectable indirect effects of cleaner fish presence on zooplankton (non-gnathiid) may partly be due to cleaners’ variable effect on planktivorous fish abundance, but also the result of invertebrate planktivory and other processes that affect zooplankton populations not investigated here. Nevertheless, the pronounced diel and temporal changes in zooplankton observed likely influence coral reef trophic interactions.

Habitat degradation drives increased gnathiid isopod ectoparasite infection rate on juvenile but not adult fish - Pauline Narvaez; Renato A. Morais; Kate S. Hutson; Mark I. McCormick; Alexandra S. Grutter (Coral Reefs, 2021)

Patterns of taxonomic and functional diversity in the global cleaner reef fish fauna - Juan P. Quimbayo; Thiago C. Mendes; Diego R. Barneche; Murilo S. Dias; Alexandra S. Grutter; Miguel Furtado; Fabien Leprieur; Loïc Pellissier; Renata Mazzei; Pauline Narvaez; Pierre Sasal; Marta C. Soares; et al. (Journal of Biogeography, 2021)
Aim Several drivers explain the global distribution of all reef fish. However, whether these drivers also explain the distribution and traits of a functional subgroup involving cleaner fishes remain unclear. Here we examine the variation in traits of cleaner fishes and test whether historical, environmental, ecological and geographical drivers are correlated with cleaner species richness and abundance at global reefs. Location Tropical and subtropical reefs. Taxon Actinopterygii. Methods We tested whether species traits and trait space vary between facultative ( i . e . species that clean only during the juvenile stages or sporadically) and dedicated ( i . e . species that clean during their whole lives) cleaner types. We compiled data from local checklists (relative richness) and belt transects (standardized richness and abundance). We built four models to test whether past and current isolation ( i . e . distance from Quaternary refugia and biodiversity centres), sea temperature, primary productivity, local species pool and abundance of potential clients influenced the relative richness and abundance of cleaners. Results Facultative cleaners had high trait variability that contributed disproportionally to the trait space, whereas dedicated cleaners exhibited low trait variability. Cleaner species richness was higher in the Indo‐Pacific and Caribbean provinces, but the relative richness and standardized abundance of cleaners were higher in the Atlantic ( i . e . North Eastern and Southwestern) and Eastern Pacific. Isolation influenced the relative richness of facultative cleaners, whereas the distance to Quaternary refugia, sea temperature and isolation influenced the relative richness of dedicated cleaners. Local species richness and standardized abundance of cleaner fish exhibited a strong relationship with regional diversity. The standardized abundance of both facultative and dedicated cleaners was influenced by the abundance of potential clients and the local species pool. Main conclusions The small trait space occupied by cleaner fishes may reflect their restricted origin among lineages of reef fishes. Differences in the relative richness and standardized abundance of cleaner fishes across marine realms suggest a strong influence on biogeographical history. Our results also indicate that cleaner fishes originated mostly in peripheral areas in high latitudes due to the absence of dedicated cleaners. Our results imply that cleaner fishes do not follow the pattern of main centres of origin described for reef fishes due to opportunistic cleaning behaviour that originated with higher frequency at locations with low species richness.

The role of corals on the abundance of a fish ectoparasite in the Great Barrier Reef - José Ricardo Paula; Derek Sun; Vasco Pissarra; Pauline Narvaez; Rui Rosa; Alexandra S. Grutter; Paul C. Sikkel (Coral Reefs, 2021)

Effect of Acute Seawater Temperature Increase on the Survival of a Fish Ectoparasite - Mary O. Shodipo; Berilin Duong; Alexia Graba-Landry; Alexandra S. Grutter; Paul C. Sikkel (Oceans, 2020)
Extreme warming events that contribute to mass coral bleaching are occurring with increasing regularity, raising questions about their effect on coral reef ecological interactions. However, the effects of such events on parasite-host interactions are largely ignored. Gnathiid isopods are common, highly mobile, external parasites of coral reef fishes, that feed on blood during the juvenile stage. They have direct and indirect impacts on their fish hosts, and are the major food source for cleaner fishes. However, how these interactions might be impacted by increased temperatures is unknown. We examined the effects of acute temperature increases, similar to those observed during mass bleaching events, on survivorship of gnathiid isopod juveniles. Laboratory experiments were conducted using individuals from one species (Gnathia aureamaculosa) from the Great Barrier Reef (GBR), and multiple unknown species from the central Philippines. Fed and unfed GBR gnathiids were held in temperature treatments of 29 °C to 32 °C and fed Philippines gnathiids were held at 28 °C to 36 °C. Gnathiids from both locations showed rapid mortality when held in temperatures 2 °C to 3 °C above average seasonal sea surface temperature (32 °C). This suggests environmental changes in temperature can influence gnathiid survival, which could have significant ecological consequences for host-parasite-cleaner fish interactions during increased temperature events.

Ocean Acidification Does Not Affect Fish Ectoparasite Survival - José Ricardo Paula; Eve Otjacques; Courtney Hildebrandt; Alexandra S. Grutter; Rui Rosa (Oceans, 2020)
The juveniles of gnathiid isopods are one of the most common fish ectoparasites in marine habitats and cause deleterious effects on fish by feeding on host blood and lymph. Reef fishes tend to engage in cooperative interactions with cleaning organisms to reduce their ectoparasite load. Ocean acidification (OA) pose multiple threats to marine life. Recently, OA was found to disrupt cleaner fish behaviour in mutualistic cleaning interactions. However, the potential effects of ocean acidification on this common ectoparasite remains unknown. Here, we test if exposure to an acidification scenario predicted by IPCC to the end of the century (RCP 8.5 – 980 μatm pCO2) affects gnathiid survival. Our results show that ocean acidification did not have any effects on gnathiid survival rate during all three juvenile life stages. Thus, we advocate that the need for cleaning interactions will persist in potentially acidified coral reefs. Nevertheless, to better understand gnathiid resilience to ocean acidification, future studies are needed to evaluate ocean acidification impacts on gnathiid reproduction and physiology as well as host-parasite interactions.

The global structure of marine cleaning mutualistic networks - Juan Pablo Quimbayo; Mauricio Cantor; Murilo S. Dias; Alexandra S. Grutter; Simon Gingins; Justine H. A. Becker; Sergio R. Floeter (Global Ecology and Biogeography, 2018)
Aim We studied the underlying biotic and abiotic drivers of network patterns in marine cleaning mutualisms (species feeding upon ectoparasites and injured tissues of others) at large spatial scales. Location Eleven marine biogeographical provinces. Time period 1971–2018. Major taxa studied Reef fish and shrimps. Methods We combined field and literature data to test whether recurrent patterns in mutualistic networks (nestedness, modularity) describe the distributions of marine cleaning interactions. Nested network structures suggest that some cleaner species interact with many clients while the others clean fewer, predictable subsets of these clients; modular network structures suggest that cleaners and clients interact within defined, densely connected subsets of species. We used linear mixed models to evaluate whether the life‐history traits of cleaners contribute to the emergence of these patterns locally and whether environmental and geographical factors influence the network structures. Results Marine cleaning networks were more nested than modular. Nestedness was prevalent in communities with dedicated cleaners (ones that feed exclusively by cleaning), whereas communities with only facultative cleaners (ones that clean opportunistically) were generally unstructured. Cleaner type and taxa were the only traits shaping networks, with dedicated fish cleaners contributing disproportionally more than facultative cleaners and shrimps to the emergence of nestedness. Although cleaner species seem concentrated around the tropics and biodiversity centres, we did not detect an influence of environmental and geographical factors on network structures. Main conclusions Dedicated species are key in shaping the structure of marine cleaning mutualistic networks. By relying exclusively on cleaning to feed, dedicated cleaners interact with most of the available clients and form the network core, whereas the opportunistic facultative species tend to clean the most common clients. We hypothesize that trophic niche variation and phenotypic specialization are major drivers of this asymmetry in marine mutualisms. Our study strengthens the links between biotic interactions at the community level and the distribution of species and specializations at larger spatial scales.

Cleaner shrimp are true cleaners of injured fish - David B. Vaughan; Alexandra S. Grutter; Hugh W. Ferguson; Rhondda Jones; Kate S. Hutson (Marine Biology, 2018)

Effects of short-term exposure to ectoparasites on fish cortisol and hematocrit levels - Zegni Triki; Alexandra S. Grutter; Redouan Bshary; Albert F. H. Ros (Marine Biology, 2016)

Equivalent cleaning in a juvenile facultative and obligate cleaning wrasse: an insight into the evolution of cleaning in labrids? - Alexandra S. Grutter; William E. Feeney (Coral Reefs, 2016)

24/7 service: nocturnal cleaning in a tropical Indo-Pacific reef - Roberta M. Bonaldo; Alexandra S. Grutter; Ivan Sazima; João Paulo Krajewski (Marine Biodiversity, 2015)

Fish mucus versus parasitic gnathiid isopods as sources of energy and sunscreens for a cleaner fish - Maxi Eckes; Sophie Dove; Ulrike E. Siebeck; Alexandra S. Grutter (Coral Reefs, 2015)

Gnathia trimaculata n. sp. (Crustacea: Isopoda: Gnathiidae), an ectoparasite found parasitising requiem sharks from off Lizard Island, Great Barrier Reef, Australia - Maryke L. Coetzee; Nico J. Smit; Alexandra S. Grutter; Angela J. Davies (Systematic Parasitology, 2009)

Experimental evidence that partner choice is a driving force in the payoff distribution among cooperators or mutualists: the cleaner fish case - Redouan Bshary; Alexandra S. Grutter (Ecology Letters, 2002)
Supply and demand largely determine the price of goods on human markets. It has been proposed that in animals, similar forces influence the payoff distribution between trading partners in sexual selection, intraspecific cooperation and interspecific mutualism. Here we present the first experimental evidence supporting biological market theory in a study on cleaner fish, Labroides dimidiatus . Cleaners interact with two classes of clients: choosy client species with access to several cleaners usually do not queue for service and do not return if ignored, while resident client species with access to only one cleaning station do queue or return. We used plexiglas plates with equal amounts of food to simulate these behaviours of the two client classes. Cleaners soon inspected ‘choosy’ plates before ‘resident’ plates. This supports previous field observations that suggest that client species with access to several cleaners exert choice to receive better (immediate) service.

Effect of the removal of cleaner fish on the abundance and species composition of reef fish - Alexandra S. Grutter (Oecologia, 1997)